Eukaryotic diversity at pH extremes - Amaral-Zettler, Linda A. (Frontiers in Microbiology, 2013)
Extremely acidic (pH<3) and extremely alkaline (pH>9) environments support a diversity of single-cell and to a lesser extent, multicellular eukaryotic life. This study compared alpha and beta diversity in eukaryotic communities from 7 diverse aquatic environments with pH values ranging from 2 to 11 using massively-parallel pyrotag sequencing targeting the V9 hypervariable region of the 18S ribosomal RNA (rRNA) gene. A total of 946 Operational Taxonomic Units (OTUs) were recovered at a 6% cut-off level (94% similarity) across the sampled environments. Hierarchical clustering of the samples segregated the communities into acidic and alkaline groups. Similarity Percentage Analysis (SIMPER) followed by Indicator OTU Analysis (IOA) and Non-metric Multidimensional Scaling (NMDS) were used to determine which characteristic groups of eukaryotic taxa typify acidic or alkaline extremes and the extent to which pH explains eukaryotic community structure in these environments. Spain’s Rio Tinto yielded the fewest observed OTUs while Nebraska Sandhills alkaline lakes yielded the most. Distinct OTUs, including metazoan OTUs, numerically dominated pH extreme sites. Indicator OTUs included the diatom Pinnularia and unidentified opisthokonts (Fungi and Filasterea) in the extremely acidic environments, and the ciliate Frontonia across the extremely alkaline sites. Inferred from NMDS, pH explained only a modest fraction of the variation across the datasets, indicating that other factors influence the underlying community structure in these environments. The findings from this study suggest that the ability for eukaryotes to adapt to pH extremes over a broad range of values may be rare, but further study of taxa that can broadly adapt across diverse acidic and alkaline environments respectively present good models for understanding adaptation and should be targeted for future investigations.